Pengelolaan Hutan Mangrove dan Pemanfaatannya dalam Meningkatkan Ekonomi Masyarakat Pesisir Pantai Provinsi Riau - Abu Bakar; Puji Purnama; Rika Rahmayuni (Lembaga penelitian dan pengabdian kepada masyrakat, 2013)
Mangrove forest is a forest type that grows along the coast almost has no canopy structure. Mangrove forests have three functions, namely: (1) physical function, namely the prevention of erosion, protection against and care various biota, various breeding places bird species and natural habitats, and (3) economic function, paper, household, textiles, as well as synthesis, leather tanning, drug - medicines, and so forth. In addition to especially in regions that are in the islands, such as in Bengkalis, and Meranti Islands Regency, Rokan Hilir, Indragiri Hulu, and Dumai in Riau province and territory which has a beach area.